Menganalisis Aspek Peningkatan Kemampuan Berpikir Kritis Siswa dalam Pembelajaran IPA - Agus Wahyudi; Hadi Purwanto (Lembaga Pengembangan Kinerja Dosen, 2024)
Critical thinking, like a double-edged sword, has become a vital tool in this tumultuous information era. On the one hand, it equips individuals with the ability to sort out accurate and reliable information amidst a sea of ​​hoaxes and manipulation. On the other hand, it opens the gates to analytical, logical and structured thinking, enabling mature and responsible decision-making. More than just a cognitive process, critical thinking is an art that requires practice and persistence. This abstract aims to dive into the sea of ​​critical thinking, examine its important elements, and explore its benefits in various aspects of life. Critical thinking is like a moral compass in the information age. By honing this ability, individuals can navigate the sea of ​​information with confidence, avoid the traps of hoaxes and manipulation, and move towards a brighter future.